Food chain allergen management : proceedings of a conference held at Leatherhead Food Research, 20 May 2009 - Emerton, Victoria (RSC Pub., 2009)
This book is the proceedings from a national conference on allergen management. Two leading research bodies, Leatherhead Food International (LFI), in conjunction with Campden BRI, hosted the conference to support the awareness and management of food allergens on the food industry. With food recalls due to cross contamination of allergens or incorrect allergen labelling an expensive problem for the food industry and dangerous for food-allergic consumers. Food Chain Allergen Management provides vital information on the tools available to enable businesses to manage allergens in the food chain. T.
Keywords: Food allergy -- Congresses.; Allergens -- Congresses.; Food contamination -- Congresses.; Food industry and trade.; Allergy.; Immunologic diseases.; Diseases.; Antigens.; Industries.; Allergens.; Food allergy.; Biological products.; elektronické knihy; electronic books